HARMONICS SURFACES OF GRAPHIC TYPE IN R3 - Carlos Carrión Riveros; Armando Vásquez Corro; Sarah O. Barbosa (Selecciones Matemáticas, 2016)
In this research we study harmonic surfaces immersed in R3. We dened Harmonic surfaces of graphic type and showed that a harmonious surface graphic type is minimal if and only if it is part of a plane or a helix. Also, we give a characterization of harmonic surfaces graphic type parameterized by asymptotic lines and some examples.